Relationship between Emotional Intelligence and Aggression on Boxers - Hande Baba Kaya; Muhsin Hazar; Malik Beyleroğlu (International Society of Philosophy and Cosmology, 2017)
Emotional Quotient is defined as the ability to perceive, use, manage and understand the emotions, which is associated with the better psychological adjustment. Analyzing studies in the literature, an inverse relationship was observed between emotional quotient and aggressive behavior. Therefore, the purpose of this study is examining the relationship between emotional quotient and aggression on boxers. This study is important for the boxers. That is why emotion management has a great role for the success in the ring. Boxing sport is based on the technical implementation. During the game boxer must control the emotions, which push him to the aggression. If emotions are not able to control during the game, anger and aggression will prevent the success. The findings of this study will demonstrate the relationship between the sports environment and emotional intelligence, in particular inferences to be made about the boxer. The sample of their search consists of 200 boxers who do sports in the districts of Eskişehir, Zonguldak, Bolu, Bursa, Ankara, Sakarya, Gaziantep and Antalya in Turkey. In this study, variation of demographic characteristics are determined Personal Information form, Bar-on Emotional Quotient Scale to determine the emotional quotient [Bar-On 1997; Acar, 2001], and Aggression Inventory were used which was developed by Kocatürk [Kocatürk, 1982]. The relationship between emotional quotient and aggression were analyzed Pearson product moment correlation coefficients. The function of emotional intelligence explanation for aggression was tested by stepwise multiple regression analysis. According to findings of the research have meaningful negative relationship between aggression and all dimensions of the emotional quotient. In addition, coping with stress and interpersonal relationships significant size aggression scores (R2 = .26, F (2,197) = 34,252, p <.001) were found to explain. As a result, boxer aggression in terms of emotional intelligence can be expressed as a factor.